Phosphogypsum road base material and preparation method thereof

By using quicklime, cement, composite curing agent and curing activaters in the phosphogypsum road base materials, the problems of low strength and poor water stability in the early stage were solved, and the phosphogypsum road base materials with high compressive strength and good water stability were achieved. , suitable for highway construction, has important environmental significance and social benefits.

CN119430836APending Publication Date: 2025-02-14CCCC WUHAN HARBOR ENG DESIGN & RES +1

Patent Information

Application Number
CN202411683670.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing phosphogypsum road base materials have low early strength and poor water stability, resulting in poor crack resistance and water stability performance, which are prone to strength loss after long-term immersion.

Method used

Using phosphogypsum as the main raw material, combined with quicklime, cement, composite curing agent and curing exciter, the use of modified phosphogypsum and atomization curing exciter promotes hydration and forms a dense mesh structure, thereby improving early strength and Water resistance.

Benefits of technology

The high compressive strength, good water stability and long-term use of the phosphogypsum road base material has been achieved. The unbounded compressive strength of 7 days is greater than 3MPa, and the unbounded compressive strength of 28 days is greater than 9.5MPa, and the water stability coefficient is as high as 126%. And the strength loss is less than 1% after multiple dry and wet cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430836A_ABST
    Figure CN119430836A_ABST
Patent Text Reader

Abstract

The invention provides an ardealite road base material and a preparation method thereof, and belongs to the field of road base materials. The road base material is prepared from the following raw materials in parts by weight: 850 to 900 parts of phosphogypsum, 5 to 15 parts of quick lime, 40 to 60 parts of cement, 55 to 85 parts of composite curing agent and 8.5 to 13 parts of curing exciting agent. The phosphogypsum is modified, so that soluble phosphorus and soluble fluorine in the phosphogypsum are cured; the curing exciting agent is atomized and added into the mixture of the modified phosphogypsum, the cement and the composite curing agent, so that all the components are in full contact, the hydration effect is promoted, and the strength and stability of the base material are improved. The pavement base material provided by the invention consumes a large amount of phosphogypsum, can effectively relieve the problem of accumulation of a large amount of phosphogypsum, reduces environmental pollution, has good mechanical properties, water stability and durability, is applied to highway construction, and has important environmental protection significance and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road base materials, and in particular to a phosphogypsum road base material and a preparation method thereof. Background Art

[0002] Phosphogypsum is a solid waste produced in the wet phosphoric acid process. Its main component is calcium sulfate dihydrate, and it also contains incompletely decomposed phosphate rock, residual phosphoric acid, fluoride, organic matter, etc. Among them, the presence of fluorine and organic matter has the greatest impact on the resource utilization of phosphogypsum. The random discharge and accumulation of phosphogypsum has seriously damaged the ecological environment, not only polluting groundwater resources, but also causing waste of land resources. At present, the main methods for consuming phosphogypsum reserves are conversion of calcium carbonate, preparation of agricultural fertilizers, use for cement and its retarder, production of building gypsum powder, building blocks, self-leveling, etc., but these methods consume limited amounts of phosphogypsum, relatively high costs and the risk of environmental pollution. Therefore, the country vigorously develops the industrialization and resource utilization of by-product gypsum, and encourages the comprehensive utilization of various by-product gypsums including phosphogypsum.

[0003] my country's highway and municipal pavement construction is developing rapidly, and a large amount of graded crushed stone, cement, asphalt, lime and other materials are consumed, which brings corresponding environmental pollution; applying a large amount of piled phosphogypsum to pavement base materials can not only consume a large amount of these solid wastes, but also reduce environmental pollution. For example, CN114751708A discloses a phosphogypsum embankment filler and its application, and a method for preparing a highway pavement base. The phosphogypsum embankment filler, by mass percentage, includes 88% to 95% phosphogypsum, 3% to 6% mineral admixture and 2% to 6% alkaline activator, and the 14d and 28d unconfined compressive strengths are 2.2Mpa and 2.9Mpa, respectively. For example, CN102690098A discloses a road subgrade filler and a preparation method thereof, which is prepared from lime, fly ash, phosphogypsum and stabilizer raw materials; the weight percentage of each raw material in lime, fly ash and phosphogypsum is: lime 4%~15%, fly ash 30%~50%, phosphogypsum 35%~60%, and the sum of the weight percentages of each raw material is 100%; the stabilizer is water glass or NaAlO2, the addition amount of water glass is 2%~6% of the total mass of lime, fly ash and phosphogypsum, and the addition amount of NaAlO2 is 0.5%~2% of the total mass of lime, fly ash and phosphogypsum. It has the problem of low early strength, and the 7d and 28d unconfined compressive strength can only reach 1.68Mpa and 1.91Mpa, and the formed road matrix is ​​too rigid and easily affected by temperature and humidity, resulting in crack resistance and water stability. Long-term immersion in water will cause serious strength loss.

[0004] Therefore, it is of great significance to provide a road base material with phosphogypsum as the main raw material, high compressive strength, good water stability and long service life. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the present invention provides a phosphogypsum road base material and a preparation method thereof. The road base material of the present invention not only consumes a large amount of stockpiled phosphogypsum, realizing high-value utilization of phosphogypsum, but also solves the problems of low early strength and poor water stability of cement-stabilized phosphogypsum base materials under the action of a composite curing agent and a curing activator. The base material prepared by the present invention has good mechanical properties, water stability and dry-wet cycle durability.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: A phosphogypsum road base material comprises the following raw materials in parts by weight: 850-900 parts of phosphogypsum, 5-15 parts of quicklime, 40-60 parts of cement, 55-85 parts of a composite curing agent and 8.5-13 parts of a curing activator.

[0007] Preferably, the cement is ordinary P·O42.5 silicate cement, and the slag is S95 grade granulated blast furnace slag.

[0008] Preferably, the composite curing agent comprises the following components in parts by weight: 50-70 parts of slag and 5-15 parts of silica fume; the preparation method is as follows: the slag and silica fume are mixed evenly.

[0009] Preferably, the curing activator comprises the following components in parts by weight: 2-3 parts of sodium methyl silicate, 2-3 parts of water glass, 0.3-0.5 parts of emulsifier, 0.1-0.2 parts of hyperdispersant, 0.1-0.2 parts of sodium phosphate and 4-6 parts of water; the preparation method is as follows: sodium methyl silicate and water glass are stirred and mixed uniformly to obtain solution I; the emulsifier, hyperdispersant and sodium phosphate are dissolved in water to obtain solution II; solution II is added to solution I, stirred uniformly, and cooled naturally to obtain solution II.

[0010] Preferably, the temperature for mixing sodium methyl silicate and water glass is 45° C.-50° C.; and the stirring time for solution I and solution II is 1-3 h.

[0011] Preferably, the emulsifier is an SDS emulsifier, and the hyperdispersant is a sodium polyacrylate dispersant.

[0012] The present invention also provides a method for preparing the above-mentioned phosphogypsum road base material, comprising the following steps: S1. Take the original phosphogypsum, crush and screen it to 1-5 mm, add water and quicklime to mix, and stew the material to obtain modified phosphogypsum; S2, preparing a curing agent activator from sodium methyl silicate, water glass, an emulsifier, a hyperdispersant, sodium phosphate and water, and performing atomization treatment; S3. After cement, slag, silica fume and modified phosphogypsum are evenly mixed, atomized curing activator is added, stirred evenly, poured into a mold, and molded and cured to obtain phosphogypsum road base material.

[0013] Preferably, in step S1, the original phosphogypsum is naturally air-dried phosphogypsum with a moisture content of no more than 15%.

[0014] Preferably, in step S1, the stewing time is 20-36 hours and the drying temperature is 45-60°C.

[0015] Preferably, in step S1, the moisture content of the modified phosphogypsum is 15%-16%.

[0016] The base material prepared according to the above technical solution has an unconfined compressive strength of more than 3MPa at 7 days, an unconfined compressive strength of more than 9.5MPa at 28 days, a water stability coefficient of up to 126% at 28 days, a strength ratio of more than 90% after 5 freeze-thaw cycles at 28 days, and a strength ratio of 99.7% after 14 dry-wet cycles at 28 days. At the same time, a large amount of phosphogypsum solid waste is consumed, which has important economic value and environmental significance.

[0017] The present invention modifies phosphogypsum to convert soluble phosphorus and fluorine in the phosphogypsum into insoluble substances, solidifies impurities in the phosphogypsum, and improves the stability of the phosphogypsum; then, an atomized curing activator is added to a mixture of cement, slag, silica fume and modified phosphogypsum that is evenly mixed, so that the curing activator is evenly dispersed, effectively combined with other components, and hydration is promoted, so that the plate-like structure of the phosphogypsum is transformed into a thin and short columnar structure, a dense network structure is formed, and early strength and water resistance are improved.

[0018] In the technical solution of the present invention, slag and silica fume have strong volcanic ash activity. Through the alkali excitation of cement and water glass, the excited slag and silica fume react with phosphogypsum to generate a large amount of hydrated calcium silicate gel and calcium sulfonite crystals. These hydration products constitute a skeleton structure, which improves the strength of the material. With the addition of a curing agent, the silanol groups in sodium methyl silicate react with the silanol groups in cement to dehydrate and cross-link, thereby forming a tightly bound, impermeable waterproof film on the surface of the phosphogypsum, reducing the influence of uncured soluble phosphorus and fluorine in the phosphogypsum on the hydration, and at the same time can also cause the material to expand slightly, increase the density of the material, and further improve the strength and water resistance of the material. The water glass further strengthens the hydration reaction, The calcium silicate and sodium sulfate formed are filled in the pores between the phosphogypsum particles and overlap each other to improve the strength of the material. At the same time, water glass has excellent bonding properties, which can block the pores of the material, increase the density, and thus improve the compressive strength of the material; emulsifiers and dispersants improve the uniformity and fluidity of the material. The two work together to significantly improve the strength, durability and stability of the phosphogypsum road base material; sodium phosphate can adjust the hydration rate of slag, silica fume and phosphogypsum, improve the water resistance and corrosion resistance of the material, and reduce the penetration of harmful substances; the combined effect of the above components makes the phosphogypsum road base material have high compressive strength, good water resistance and corrosion resistance, as well as excellent stability and durability.

[0019] The present invention has the following beneficial effects: 1. The present invention adopts quicklime neutralization method to solidify soluble phosphorus and soluble fluorine in phosphogypsum, thereby eliminating the problems of long setting time and low strength when using phosphogypsum to prepare road base materials; by adding atomized curing activator to a mixture of uniformly mixed cement, slag, silica fume and modified phosphogypsum, the components are fully contacted to promote hydration, and at the same time, a waterproof film is formed on the surface of phosphogypsum to prevent phosphogypsum from dissolving in water, thereby improving the strength and water stability of road base materials and enhancing durability.

[0020] 2. The road base material prepared by the present invention has an unconfined compressive strength of greater than 3 MPa at 7 days, an unconfined compressive strength of greater than 9.5 MPa at 28 days, a water stability coefficient of up to 126% at 28 days, a strength ratio of more than 90% after 5 freeze-thaw cycles at 28 days, a strength ratio of 99.7% after 14 dry-wet cycles at 28 days, a fluoride content of less than 0.5 mg / L in the leachate, and a total phosphorus content of less than 0.18 mg / L.

[0021] 3. The present invention consumes a large amount of phosphogypsum in preparing road base materials, which can effectively alleviate the problem of large-scale accumulation of phosphogypsum, realize the resource utilization of phosphogypsum, and reduce environmental pollution. In addition, the prepared base material has good mechanical properties and water stability, and is applied in highway construction, which has important environmental protection significance and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the 28d SEM image of the base material after the original phosphogypsum was cured; In the figure: a is a SEM image at a magnification of 500×, and b is a SEM image at a magnification of 10000×; Figure 2 This is the 28d SEM image of the base material after curing of the present invention; In the figure: a is a SEM image with a magnification of 500×, and b is a SEM image with a magnification of 5000×. DETAILED DESCRIPTION

[0023] Embodiment 1: A phosphogypsum road base material, comprising the following raw materials: 850 kg of phosphogypsum, 5 kg of quicklime, 40 kg of cement, 50 kg of slag, 5 kg of silica fume, and 8.5 kg of a curing activator; Among them, the curing agent activator is 2kg of sodium methyl silicate, 2kg of water glass, 0.3kg of SDS emulsifier, 0.1kg of sodium polyacrylate dispersant, 0.1kg of sodium phosphate and 4kg of water; the preparation method is as follows: sodium methyl silicate and water glass are mixed at 45°C to obtain solution I; SDS emulsifier, sodium polyacrylate dispersant and sodium phosphate are dissolved in water to obtain solution II; solution II is added dropwise to solution I with a peristaltic pump, stirred for 1.5 hours, and cooled naturally to obtain the solution.

[0024] The method for preparing a phosphogypsum road base material comprises the following steps: S1. Take naturally air-dried phosphogypsum, crush and screen it to 1-5 mm, add quicklime and water to mix, and stew for 24 hours to obtain modified phosphogypsum with a moisture content of 15%; S2, preparing a curing agent activator from sodium methyl silicate, water glass, SDS emulsifier, sodium polyacrylate super dispersant, sodium phosphate and water, and atomizing the mixture; S3. After cement, slag, silica fume and modified phosphogypsum are evenly mixed, atomized curing activator is added, stirred evenly, poured into a mold, and molded and cured to obtain phosphogypsum road base material.

[0025] Embodiment 2: A phosphogypsum road base material, comprising the following raw materials in parts by weight: 900 kg of phosphogypsum, 15 kg of quicklime, 60 kg of cement, 70 kg of slag, 15 kg of silica fume, and 12.9 kg of a curing activator; Among them, the curing activator is 3kg of sodium methyl silicate, 3kg of water glass, 0.5kg of SDS emulsifier, 0.2kg of sodium polyacrylate dispersant, 0.2kg of sodium phosphate and 6kg of water; the preparation method is as follows: sodium methyl silicate and water glass are mixed at 50°C to obtain solution I; SDS emulsifier, sodium polyacrylate dispersant and sodium phosphate are dissolved in water to obtain solution II; solution II is added dropwise to solution I with a peristaltic pump, stirred for 2.5 hours, and cooled naturally to obtain.

[0026] The method for preparing a phosphogypsum road base material comprises the following steps: S1. Take naturally air-dried phosphogypsum, crush and screen it to 1-5 mm, add quicklime and water to mix, and stew for 24 hours to obtain modified phosphogypsum with a moisture content of 15%; S2, preparing a curing agent activator from sodium methyl silicate, water glass, SDS emulsifier, sodium polyacrylate super dispersant, sodium phosphate and water, and atomizing the mixture; S3. After cement, slag, silica fume and modified phosphogypsum are evenly mixed, atomized curing activator is added, stirred evenly, poured into a mold, and molded and cured to obtain phosphogypsum road base material.

[0027] Embodiment 3: A phosphogypsum road base material, comprising the following raw materials in parts by weight: 870 kg of phosphogypsum, 10 kg of quicklime, 50 kg of cement, 60 kg of slag, 10 kg of silica fume, and 10.5 kg of a curing activator; Among them, the curing activator is 2.4kg of sodium methyl silicate, 2.4kg of water glass, 0.4kg of SDS emulsifier, 0.15kg of sodium polyacrylate dispersant, 0.15kg of sodium phosphate and 5kg of water; the sodium methyl silicate and water glass are mixed at 47°C to obtain solution I; the SDS emulsifier, sodium polyacrylate dispersant and sodium phosphate are dissolved in water to obtain solution II; solution II is added dropwise to solution I with a peristaltic pump, stirred for 2 hours, and cooled naturally to obtain the solution.

[0028] The method for preparing a phosphogypsum road base material comprises the following steps: S1. Take naturally air-dried phosphogypsum, crush and screen it to 1-5 mm, add quicklime and water to mix, and stew for 24 hours to obtain modified phosphogypsum with a moisture content of 15%; S2, preparing a curing agent activator from sodium methyl silicate, water glass, SDS emulsifier, sodium polyacrylate super dispersant, sodium phosphate and water, and atomizing the mixture; S3. After cement, slag, silica fume and modified phosphogypsum are evenly mixed, atomized curing activator is added, stirred evenly, poured into a mold, cured and formed, and the phosphogypsum road base material is obtained.

[0029] Comparative Example 1: The same as Example 2, the only difference is that the curing activator does not contain sodium methyl silicate.

[0030] Comparative Example 2: The same as Example 2, the only difference is that the curing activator does not contain water glass.

[0031] Comparative Example 3: The same as Example 2, the only difference is that the curing activator does not contain sodium phosphate.

[0032] Comparative Example 4: The same as Example 2, the only difference is that in step S1, quicklime is not added to the crushed and screened phosphogypsum.

[0033] Comparative Example 5: The method is the same as Example 2, except that: in step S1, the naturally air-dried phosphogypsum is not crushed and screened; and in step S2, the curing activator is not atomized.

[0034] The unconfined compressive strength, water stability coefficient, dry-wet cycle coefficient and harmful substance precipitation of the phosphogypsum road base materials of the above embodiment and comparative example were tested respectively, and the specific results are as follows: Table 1 Performance parameters of phosphogypsum road base materials of embodiments and comparative examples

[0035] Note: A water stability coefficient exceeding 100% indicates that the strength of the water-cured specimen increases faster as the curing age increases.

[0036] As shown in Table 1, the performance of the base material prepared in Comparative Examples 1-3 is slightly worse than that in Example 2 by reducing the components of the curing activator; as shown in Examples 1-3, the performance of the base material is gradually enhanced by increasing the amount of the composite curing agent and the curing activator, but the cost of the curing activator is relatively high, resulting in an increase in the cost of preparing the base material. Compared with Comparative Examples 4-5, Example 2 uses modified phosphogypsum and atomized curing activator to make the prepared base material have better mechanical properties and water stability. In Examples 2-3, the 7d unconfined compressive strength of the base material is as high as 3.96MPa, and the water stability coefficient of 14d is much greater than 80%, indicating good water stability; the fluoride concentration in the 28d leachate of the base material is less than 0.5mg / L, and the total phosphorus concentration is less than 0.2mg / L, which meets the standard requirements of Class V water bodies in the "Surface Water Environmental Quality Standard" (GB3838-2002); after multiple dry-wet cycles, the strength loss of the base material prepared by the present invention is less than 1%.

[0037] Figure 1 and Figure 2They are respectively the 28d SEM image of the base material prepared after the original phosphogypsum is solidified and the 28d SEM image of the base material prepared after the phosphogypsum of the present invention is solidified. Figure 1 It can be seen that when the original phosphogypsum is used to participate in the reaction, although the hydration product covers the surface of the phosphogypsum in the later stage, some phosphogypsum that is not covered can still be seen, and there are many cracks; Figure 2 In the present invention, after the phosphogypsum is solidified, the density of the hardened base material prepared is significantly better than Figure 1 In the later stage of hydration, there are fewer surface cracks and more hydration products. Some needle-rod-shaped calcium sulfonate crystals and gel-like CSH can also be found. The CSH gel bonds the incompletely hydrated phosphogypsum. The calcium sulfonate is interspersed and bonded between the CSH gels and on the surface of the incompletely hydrated phosphogypsum. The CSH gel gradually wraps other hydration products to make the structure denser.

[0038] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.

Claims

1. A phosphogypsum road base material, characterized in that: The base material comprises the following raw materials in parts by weight: 850-900 parts of phosphogypsum, 5-15 parts of quicklime, 40-60 parts of cement, 55-85 parts of composite curing agent and 8.5-13 parts of curing activator.

2. The phosphogypsum road base material according to claim 1, characterized in that: The cement is P·O42.5 silicate cement, and the slag is S95 grade granulated blast furnace slag.

3. The phosphogypsum road base material according to claim 1, characterized in that: The composite curing agent comprises the following components in parts by weight: 50-70 parts of slag and 5-15 parts of silica fume.

4. The phosphogypsum road base material according to claim 1, characterized in that: The curing activator comprises the following components in parts by weight: 2-3 parts of sodium methyl silicate, 2-3 parts of water glass, 0.3-0.5 parts of emulsifier, 0.1-0.2 parts of hyperdispersant, 0.1-0.2 parts of sodium phosphate and 4-6 parts of water.

5. The phosphogypsum road base material according to claim 4, characterized in that: The preparation method of the curing activator is as follows: sodium methyl silicate and water glass are stirred and mixed to obtain solution I; emulsifier, hyperdispersant and sodium phosphate are dissolved in water to obtain solution II; solution II is added to solution I, stirred evenly, and cooled naturally to obtain the curing activator.

6. The phosphogypsum road base material according to claim 4, characterized in that: The mixing temperature of sodium methyl silicate and water glass is 45-50° C.; the stirring time of solution I and solution II is 1-3 hours.

7. The phosphogypsum road base material according to claim 4, characterized in that: The emulsifier is SDS emulsifier, and the hyperdispersant is sodium polyacrylate dispersant.

8. The method for preparing the phosphogypsum road base material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. After crushing and screening the original phosphogypsum to 1-5 mm, adding water and quicklime to mix evenly, and then stewing the material to obtain modified phosphogypsum; S2, preparing a curing agent activator from sodium methyl silicate, water glass, an emulsifier, a hyperdispersant, sodium phosphate and water, and performing atomization treatment; S3. After cement, slag, silica fume and modified phosphogypsum are evenly mixed, atomized curing activator is added, stirred evenly, poured into a mold, and molded and cured to obtain phosphogypsum road base material.

9. The method for preparing the phosphogypsum road base material according to claim 8, characterized in that: In the step S1, the original phosphogypsum is naturally air-dried phosphogypsum with a moisture content of no more than 15%.

10. The method for preparing the phosphogypsum road base material according to claim 8, characterized in that: The moisture content of modified phosphogypsum in S1 is 15%-16%.

Citation Information

Patent Citations

  • Roadbed filler for road and preparation method of roadbed filler

    CN102690098A

  • Phosphogypsum embankment filler, application thereof and preparation method of highway pavement base course

    CN114751708A

Cited By

  • Undisturbed phosphogypsum curing modifier as well as preparation method and application thereof

    CN120097662A

  • Ardealite harmless treatment device, treatment process and application of ardealite harmless treatment device

    CN120481077A

  • Phosphogypsum harmless treatment device, treatment process and application thereof

    CN120481077B

  • High-content phosphogypsum pavement base material and preparation method thereof

    CN120794554A

  • High-content phosphogypsum pavement base material and preparation method thereof

    CN120794554B